Entre o canavial e o porto : identidades e trajetórias dos trabalhadores rurais na zona da mata sul de Pernambuco - Maciel, Jeanne Mariel Brito de Moura (2016)
The Zona da Mata Sul of Pernambuco has undergone transformations in its productive sector, mainly as a result of the restructuring of the sugar cane monoculture sector, which has been constantly fluctuating in relation to profits and productivity since the mid-1990s. In addition, there was the growth in the years 2000 of a new productive actor in the locality, the Industrial Port Complex of Suape. Despite being created between 1976-1978, port enterprises – with about 100 companies installed that generate 25,000 direct jobs – became more intense with the creation of the Growth Acceleration Program (PAC) in 2007 under the government of Former President Lula. Thus, if before the advent of Suape the supply of employment in the region – for its majority rural population – came from of the cane fields and sugar industry, now the presence of this new element brought with it new possibilities of living in the place. This situation has been accompanied by the mobility of the productive force – of which Gaudemar speaks – of hundreds of cane workers for employment in the largest companies in the port of Suape, especially those in the construction sector and companies in the naval area, such as the Shipyard Atlantic South and Vard Promar Shipyard. In this context, the construction of the research sought to understand this dynamics and the possible implications of this displacement on the living space of the social actors who experienced this process. Thus, the aim of this thesis is to analyze the possible transformations in the identities and, therefore, in the trajectories of the rural workers of zona da mata sul canavieira of Pernambuco given the presence of Suape. and, as specific objectives: a) to describe the profile of these workers with regard to gender, age, schooling and origin; b) characterize how the insertion of workers occurs in the Suape complex; c) analyze the identity mediation of rural workers in face of the change of condition of rural workers to workers in the industries of Porto of Suape; d) to show how the workers perceive the transformations that they are experiencing in their ways of life and, if consequently, there are changes in their projects of life. As a methodological resource, I make use of qualitative research and semi-structured interviews with a focus on the life history of social actors. Workers from the municipalities of Sirinhaém, Ribeirão, Escada, Rio Formoso and Ipojuca were interviewed. Also interviews were conducted with leaders of rural unions, employers and agents of the government of the state of Pernambuco. The documentary source was very useful in order to confirm the information collected in the interviews, as well as the bibliographic survey that enabled the construction of key concepts for the interpretation and analysis of the data.